The P2X7 Receptor Is Involved in Diabetic Neuropathic Pain Hypersensitivity Mediated by TRPV1 in the Rat Dorsal Root Ganglion - Anhui Wang (Frontiers in Molecular Neuroscience, 2021)
The purinergic 2X7 (P2X7) receptor expressed in satellite glial cells (SGCs) is involved in the inflammatory response, and transient receptor potential vanilloid 1 (TRPV1) participates in the process of neurogenic inflammation, such as that in diabetic neuropathic pain (DNP) and peripheral neuralgia. The main purpose of this study was to explore the role of the P2X7 receptor in DNP hypersensitivity mediated by TRPV1 in the rat and its possible mechanism. A rat model of type 2 diabetes mellitus-related neuropathic pain (NPP) named the DNP rat model was established in this study. The mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) of DNP rats were increased after intrathecal injection of the P2X7 receptor antagonist A438079, and the mRNA and protein levels of TRPV1 in the dorsal root ganglion (DRG) were decreased in DNP rats treated with A438079 compared to untreated DNP rats; in addition, A438079 also decreased the phosphorylation of p38 and extracellular signal-regulated kinase 1/2 (ERK1/2) in the DNP group. Based on these results, the P2X7 receptor might be involved in DNP mediated by TRPV1.